2011
DOI: 10.1111/j.1538-7836.2010.04131.x
|View full text |Cite
|
Sign up to set email alerts
|

The platelet contribution to cancer progression

Abstract: Summary. Traditionally viewed as major cellular components in hemostasis and thrombosis, the contribution of platelets to the progression of cancer is an emerging area of research interest. Complex interactions between tumor cells and circulating platelets play an important role in cancer growth and dissemination, and a growing body of evidence supports a role for physiologic platelet receptors and platelet agonists in cancer metastases and angiogenesis. Platelets provide a procoagulant surface facilitating am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
503
2
27

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 596 publications
(535 citation statements)
references
References 153 publications
(157 reference statements)
3
503
2
27
Order By: Relevance
“…Preoperative PLT was negatively associated with the amount of transfused platelets during surgery (coefficient -0.49; P < 0.001), during the first week after surgery (coefficient -0.55; P < 0.001), and between 1 and 2 weeks after surgery (coefficient -0.21; P < 0.001). Accordingly, the amount of transfused platelets during surgery, during the first week after surgery, and between 1 and 2 weeks after surgery was 0 (0-6), 9 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), and 0 (0-0) units in the low platelet group and 0 (0-0), 0 (0-4), and 0 (0-0) units in the high platelet group, respectively, where 1 unit of apheresis platelets was considered to be equivalent to 6 units of platelets, as described previously. (22) Minimum PLT measured at each postoperative day during the first 2 weeks after transplantation was consistently <30 3 10 9 /L in median within the subgroup of recipients who underwent platelet transfusion on each corresponding day, indicating that platelet transfusion was performed according to our standardized protocol targeting PLT >30 3 10 9 /L (Supporting Fig.…”
Section: Association Between Perioperative Plt and Platelet Transfusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative PLT was negatively associated with the amount of transfused platelets during surgery (coefficient -0.49; P < 0.001), during the first week after surgery (coefficient -0.55; P < 0.001), and between 1 and 2 weeks after surgery (coefficient -0.21; P < 0.001). Accordingly, the amount of transfused platelets during surgery, during the first week after surgery, and between 1 and 2 weeks after surgery was 0 (0-6), 9 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), and 0 (0-0) units in the low platelet group and 0 (0-0), 0 (0-4), and 0 (0-0) units in the high platelet group, respectively, where 1 unit of apheresis platelets was considered to be equivalent to 6 units of platelets, as described previously. (22) Minimum PLT measured at each postoperative day during the first 2 weeks after transplantation was consistently <30 3 10 9 /L in median within the subgroup of recipients who underwent platelet transfusion on each corresponding day, indicating that platelet transfusion was performed according to our standardized protocol targeting PLT >30 3 10 9 /L (Supporting Fig.…”
Section: Association Between Perioperative Plt and Platelet Transfusionmentioning
confidence: 99%
“…(9) The relationship between platelets and tumors is not a simple epiphenomenon resulting from tumor-induced thrombopoiesis, but rather a direct contribution of platelets to multiple steps in the cancer progression, including tumor cell angiogenesis, protection from immune attack, extravasation, and arrest within the vasculature. (6,7,10,11) A previous study in hepatitis B virus (HBV) transgenic mice clearly demonstrated that antiplatelet treatment reduced intrahepatic inflammatory response and HCC development with improved longterm survival. (12) Thus, we hypothesized that the risk of HCC recurrence after living donor liver transplantation is affected by platelets.…”
mentioning
confidence: 99%
“…The specific contribution of the platelet P2 receptors in this disease warrants further studies as the P2Y 1 receptor has also been proposed to have a role in airways inflammation [143]. Platelets are strongly involved in cancer and especially in metastatic dissemination [144,145] through complex mechanisms including the ability to mask tumour cells to the immune system and to contribute to tumoural angiogenesis. In particular, tumour cells release nucleotides which, among other stimuli, activate platelets.…”
Section: The P2y 1 Receptor As a Target For New Antiplatelet Compoundsmentioning
confidence: 99%
“…5-HT has been demonstrated to have angiogenic potential. Therefore, we assessed if 5-HT could activate certain angiogenic signaling kinases.…”
Section: -Ht Activates Signaling Kinases In Human Endothelial Cellsmentioning
confidence: 99%